2013
DOI: 10.1371/journal.pone.0077081
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Mycobacterium tuberculosis Protein Tyrosine Phosphatase B (PtpB) Inhibitors from Natural Products

Abstract: Protein tyrosine phosphatase B (PtpB) is one of the virulence factors secreted into the host cell by Mycobacterium tuberculosis. PtpB attenuates host immune defenses by interfering with signal transduction pathways in macrophages and, therefore, it is considered a promising target for the development of novel anti-tuberculosis drugs. Here we report the discovery of natural compound inhibitors of PtpB among an in house library of more than 800 natural substances by means of a multidisciplinary approach, mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 44 publications
2
53
0
1
Order By: Relevance
“…Figure 6 shows that PtpB activity is optimum at 37 o C and pH of 6.0. These findings are in agreement to the previous reports (Mascarello et al, 2013;Chiaradia et al, 2008). Thus the recovered PtpB produced by this approach is ready to be utilized in the further study, such as screening of novel inhibitors for PtpB.…”
Section: Determination Of Optimum Ptpb Activitysupporting
confidence: 92%
“…Figure 6 shows that PtpB activity is optimum at 37 o C and pH of 6.0. These findings are in agreement to the previous reports (Mascarello et al, 2013;Chiaradia et al, 2008). Thus the recovered PtpB produced by this approach is ready to be utilized in the further study, such as screening of novel inhibitors for PtpB.…”
Section: Determination Of Optimum Ptpb Activitysupporting
confidence: 92%
“…More recently, Zhou et al, (2010) proposed that PtpB promotes mycobacterial survival in cultures of macrophages by inhibiting extracellular signal-regulated kinase 1/2 (ERK1/2) and p38 pathways, and by increasing the phosphorylation of Akt, resulting in reduced production of interleukin-6 and decreased apoptotic activity, respectively. Molecular docking, rescoring, and visual inspection was used by Mascarello et al (2013) to prioritize several natural compounds as possible PtpB inhibitors. Based on the in silico calculations, 14 compounds were selected for biological investigations in vitro.…”
Section: Protein Tyrosine Phosphatase B Inhibitorsmentioning
confidence: 99%
“…Indeed, peptide mass fingerprint analyses performed by mass spectrometry showed that Kuwanol E was able to protect the PtpB catalytic site against the proteolytic activity of trypsin, thus reinforcing the proposed notion that this inhibitor may interact within the PtpB catalytic site. Mascarello et al (2013) opine that the possible binding mode of KuwE with PtpB, investigated by molecular docking, is via hydroxyl groups of KuwE performing H-bond interactions with the catalytic site of PtpB. The MIC value of the investigated compound was, however, not assessed.…”
Section: The Schematic Mode Of Action Of Outer Membrane Inhibitorsmentioning
confidence: 99%
“…Selected structures were further filtered with the FILTER application of OpenEye 25 for the presence of the carboxylate moiety and the protonation state of each molecule was assigned by using the FIXPKA application of QUACPAC of OpenEye 26 . Conformational analysis of the database was carried out with the OMEGA software of OpenEye (Santa Fe, NM) 27,28 , by keeping a maximum of 500 conformations for each molecule. Molecular docking was performed by means of the FRED software (Santa Fe, NM) implemented in the OEDocking suite of OpenEye 29 , by saving the best five poses for each molecule and only for the first 50 best scored molecules.…”
Section: Molecular Dockingmentioning
confidence: 99%